Sharing and cultivating tacit knowledge in an online learning environment - Tee, M.Y.; Karney, D. (Springer, 2010)
Research on knowledge cultivation often focuses on explicit forms of knowledge. However, knowledge can also take a tacit form-a form that is often difficult or impossible to tease out, even when it is considered critical in an educational context. A review of the literature revealed that few studies have examined tacit knowledge issues in online learning environments. The purpose of this study was to develop a greater understanding of the conditions and processes that help promote the sharing or cultivation of tacit knowledge in a formal online course setting. Using naturalistic inquiry as the methodology of this study, an online graduate business course offered at a private, non-profit United States-based university was purposively selected as the research site. The study found that the online course encouraged processes and created conditions consistent with Nonaka's model of knowledge creation and the concept of ba (or shared context)-encouraging students to share, and to construct knowledge through socialization, externalization, combination, and internalization. The results suggest that purposefully developing a ba-like environment may be a useful approach to facilitating online learning, creating a strong potential to support learning processes necessary for students to cultivate tacit knowledge.